Legal Protection of Tobacco Farmers in Indonesia - Agus Dono Wibawanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Tobacco and processed tobacco products is not only being an important part in the culture of the Indonesian nation. But they are also natural biological resources which have contributed greatly to the prosperity and welfare of the Indonesian people. Basically entrepreneurs or farmers of the Tobacco Industry as a very strategic trading eye have a very big role on the country's economy and the household economy of the Indonesian people specifically tobacco farmers. The cigarette and tobacco industry is one of the national industries that is still quite strong to date, in addition to material contributions in the form of state revenue from excise and employment, this tobacco-based industry is recognized as being part of the Indonesian community. This industry involves directly or indirectly. Nicotine in cigarettes is a group of legal addictive substances such as cigarettes, cigars, nicotine pieces which are stimulants, which increase dopamine and adrenaline. The main research question in this research is how is legal protection for tobacco farmers in the perspective of the Law of the Republic of Indonesia Number 36 of 2009 concerning Health? The research method used is normative legal research, using analysis of various legal materials. By using normative legal research methods because to produce new arguments, theories or concepts as a prescription in solving the problems faced, namely Legal Protection against Tobacco Farmers. The conclusions of this study are efforts to protect against the dangers of smoking, among others, by raising the price of cigarettes, prohibiting the sale of cigarettes to children less than 18 years and prohibiting the sale of cigarette bars and not ratifying the Framework Convention on Tobaco Control (FCTC).